Relationship between single-leg balance, single-leg hop, and agility running performance in female field hockey players: Implications for lower extremity injury prevention screening - Kempfert, D. J.; Clacher, L. H.; Clark, N. C. (Physical Therapy in Sport, 2025)
Objectives In field hockey, there is limited information regarding lower extremity (LE) injury prevention screening protocols. To help inform the design of field hockey LE injury prevention screening protocols, the purpose of this study was to investigate whether static and dynamic single-leg balance (SLB), single-leg hop (SLH), and agility running tasks with unilateral limb-loading bias capture similar or different aspects of LE motor performance.